Potential Alphavirus Inhibitors From Phytocompounds – Molecular Docking and Dynamics Based Approach - Maneesha Sharma; Anu Bansal; Shikha Suman; Neeta Raj Sharma (Innovative Biosystems and Bioengineering, 2023)
Background. Alphaviral diseases are an economic burden all over the world due to their chronicity and distribution worldwide. The glycoproteins E1 and E2 are important for binding to the surface of the host cell by interacting with the receptors and non-structural proteins named nsP2 and nsP4 are important for the replication of virus, so can be an important drug discovery target.